2019
DOI: 10.1128/aac.01586-18
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Novel pmrB and eptA Mutations in Isogenic Acinetobacter baumannii Isolates Associated with Colistin Resistance and Increased Virulence In Vivo

Abstract: Colistin resistance in Acinetobacter baumannii is of great concern and is a threat to human health. In this study, we investigate the mechanisms of colistin resistance in four isogenic pairs of A. baumannii isolates displaying an increase in colistin MICs. A mutation in pmrB was detected in each colistin-resistant isolate, three of which were novel (A28V, I232T, and ΔL9-G12). Increased expression of pmrC was shown by semi-quantitative reverse transcription-PCR (qRT-PCR) for three colistin-resistant isolates, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 46 publications
7
65
0
Order By: Relevance
“…Similarly, the two ColS isolates from our study had pmrCAB alterations and a modified lipid A, as observed with mass spectrometry. All these observations support the hypothesis that additional and still unknown factors are involved in colistin resistance of clinical A. baumannii isolates (Jeannot et al, 2017;Gerson et al, 2019Gerson et al, , 2020. Determination of the cellenvelope charge could be useful in the elucidation process of the complex mechanism of colistin resistance in A. baumannii (Cafiso et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similarly, the two ColS isolates from our study had pmrCAB alterations and a modified lipid A, as observed with mass spectrometry. All these observations support the hypothesis that additional and still unknown factors are involved in colistin resistance of clinical A. baumannii isolates (Jeannot et al, 2017;Gerson et al, 2019Gerson et al, , 2020. Determination of the cellenvelope charge could be useful in the elucidation process of the complex mechanism of colistin resistance in A. baumannii (Cafiso et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Colistin resistance may also result from the overexpression of etpA, a pmrC homolog. This is mediated by insertional inactivation of a gene encoding an H-NS family transcriptional regulator (Lucas et al, 2018) or by integration of insertion sequence elements upstream of the eptA gene itself (Gerson et al, 2019;Potron et al, 2019;Trebosc et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This resistance is often associated with changes in the expression of regulators affecting LPS production. For example, the addition of phosphoethanolamine (PE) to lipid A due to overexpression of pmrC results in a substantial reduction of colistin binding as the negative charge of the LPS is hugely lowered (37).…”
Section: Antibiotic Resistance Mechanisms and Prioritization Of Antibmentioning
confidence: 99%
“…In particular, two amino acid alterations in eptA (T148A and K233T) are probably associated with overexpression on the gene, which results in colistin resistance, because the strains with the mutations (E154R, QIA32, QIA33, and EC111) showed obvious high expression of eptA. The association of eptA mutation and colistin resistance has been suggested in several Gram-negative bacteria, including E. coli, K. pneumoniae, and A. baumannii (Lesho et al, 2013;Mathur et al, 2018;Xu et al, 2018;Gerson et al, 2019). The high variation of eptA in E139R may be due to genetic exchange of chromosomal portions including eptA, but its donor could not be identified.…”
Section: Discussionmentioning
confidence: 99%